Chronic Sulfasalazine Treatment in Mice Induces System xc− - Independent Adverse Effects - Verbruggen, Lise; Sprimont, Lindsay; Bentea, Eduard; Janssen, Pauline; Gharib, Azzedine; Deneyer, Lauren; De Pauw, Laura; Lara, Olaya; Sato, Hideyo; Nicaise, Charles; Massie, Ann (Frontiers in Pharmacology, 2021)
Despite ample evidence for the therapeutic potential of inhibition of the cystine/glutamate antiporter system xc- in neurological disorders and in cancer, none of the proposed inhibitors is selective. In this context, a lot of research has been performed using the EMA- and FDA-approved drug sulfasalazine (SAS). Even though this molecule is already on the market for decades as an anti-inflammatory drug, serious side effects due to its use have been reported. Whereas for the treatment of the main indications, SAS needs to be cleaved in the intestine into the anti-inflammatory compound mesalazine, it needs to reach the systemic circulation in its intact form to allow inhibition of system xc-. The higher plasma levels of intact SAS (or its metabolites) might induce adverse effects, independent of its action on system xc-. Some of these effects have however been attributed to system xc- inhibition, calling into question the safety of targeting system xc-. In this study we chronically treated system xc- - deficient mice and their wildtype littermates with two different doses of SAS (160mg/kg twice daily or 320mg/kg once daily, i.p.) and studied some of the adverse effects that were previously reported. SAS had a negative impact on the survival rate, the body weight, the thermoregulation and/or stress reaction of mice of both genotypes, and thus independent of its inhibitory action on system xc-. While SAS decreased the total distance travelled in the open-field test the first time the mice encountered the test, it did not influence this parameter on the long-term and it did not induce other behavioral changes such as anxiety- or depressive-like behavior. Finally, no major histological abnormalities were observed in the spinal cord. To conclude, we were unable to identify any undesirable system xc-- dependent effect of chronic administration of SAS.